Effect of micro-cracks on the angiogenesis and osteophyte development during degenerative joint disease - Bednarczyk, Ewa Irena; Lekszycki, Tomasz; Glinkowski, Wojciech (Computer Assisted Methods in Engineering and Science; Vol 24 No 3 (2017), 2018)
Osteoarthritis, one of the most common types of arthritis, is characterized by the development of osteophytes. The main cause of joint degeneration is mechanical loading, but there are also several other factors that influence the development of osteophytes. In order to formulate a mathematical model of bone spurs’ development we have selected the most important factors, such as angiogenesis, micro-damage of the tissue structure and cell signaling. The proposed system of integro-differential equations describes the degenerative changes in the joint. Numerical calculations were implemented into the COMSOL Multiphysics software and the obtained results thus reflect relationships between certain parameters and variables. Additionally, the results correspond with those obtained from medical observations.